2008
DOI: 10.1111/j.1365-2044.2008.05487.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different analgesic regimens on transcutaneous CO2 after major surgery

Abstract: Summary Ventilatory impairment may be detected by a rise in transcutaneous carbon dioxide levels (PtcCO2). This observational study assessed the clinical utility of PtcCO2 monitoring in the postoperative period, and quantified the effect of different peri‐operative analgesic regimens on postoperative respiratory function. Following pre‐operative baseline PtcCO2 recording, continuous PtcCO2 monitoring was performed in 30 patients after major colorectal surgery for up to 24 h. Mean postoperative values of PtcCO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Kopka et al [116] and McCormack et al [117] showed that tcPCO 2 was useful to detect hypoventilation by analgesia after surgery. However, they had no any other monitors, as a control to compare with tcPCO 2 , therefore, its usefulness is questionable.…”
Section: Percutaneous Oxygen and Carbon Dioxide Tensionmentioning
confidence: 99%
“…Kopka et al [116] and McCormack et al [117] showed that tcPCO 2 was useful to detect hypoventilation by analgesia after surgery. However, they had no any other monitors, as a control to compare with tcPCO 2 , therefore, its usefulness is questionable.…”
Section: Percutaneous Oxygen and Carbon Dioxide Tensionmentioning
confidence: 99%
“…Cases of respiratory depression related to the use of basal infusions with PCA use have been reported [8][9][10][11]. The risk of respiratory depression was studied by analyzing which background infusion rates were associated with the greatest risk.…”
Section: Introductionmentioning
confidence: 99%
“…Within our department we have looked specifically at transcutaneous PCO 2 (P tc CO 2 ) measurements in the first 24 h following major colorectal surgery and the effect that morphine PCA and epidural analgesia have on ventilation . Our findings revealed a mean (95% CI) postoperative P tc CO 2 of 5.6 (5.0–6.1) kPa in the epidural group compared with 6.7 (6.2–7.2) kPa in the PCA group, representing a significant increase over baseline P tc CO 2 in the PCA group of 1.8 (1.5–2.1) kPa compared with 0.7 (0.5–0.9) kPa in the epidural group.…”
mentioning
confidence: 89%